Aplikasi Layanan Bebas Pustaka Berbasis Web terhadap Kepuasan Pemustaka di Perpustakaan Universitas Hasanuddin Makassar - Andi Nur Fadilah; Iskandar Iskandar; Umar Sulaiman (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to analyze the level of user satisfaction and the impact of a web-based library clearance service application on user satisfaction at the Library of Hasanuddin University, Makassar. A descriptive quantitative method was used with 99 respondents, all of whom were students who had used the application. Data were collected through an online questionnaire and analyzed using SPSS and Microsoft Excel. The results show that user satisfaction with the application is categorized as "very satisfied," with a satisfaction percentage of 82%. Based on the End-User Computing Satisfaction (EUCS) model, the highest score was found in the content variable (90%), followed by accuracy (85%), format (83%), ease of use (80%), and timeliness (77%). The findings also indicate that the web-based application has a significant impact on user satisfaction. This study recommends the addition of features such as clearance letter extension, notifications, and other relevant tools to meet user needs. The results are expected to serve as a reference for future research and the development of library services based on information technology.